2011
DOI: 10.1007/s00213-011-2211-x
|View full text |Cite
|
Sign up to set email alerts
|

Association of genetic variants of the histamine H1 and muscarinic M3 receptors with BMI and HbA1c values in patients on antipsychotic medication

Abstract: RationaleAntipsychotic affinity for the histamine H1 receptor and the muscarinic M3 receptor have been associated with the side effects weight gain, and development of diabetes, respectively.ObjectivesWe investigated polymorphisms of the histamine H1 (HRH1) and muscarinic acetylcholine receptor M3 (CHRM3) receptor genes for an association with body mass index (BMI) and glycated hemoglobin (HbA1c).MethodsWe included 430 Caucasian patients with a non-affective psychotic disorder using antipsychotics for at least… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 47 publications
0
31
0
4
Order By: Relevance
“…Olanzapine treatment upregulated mRNA expression and protein levels of hypothalamic H 1 R, which was correlated with hyperphagia and weight gain induced by olanzapine [56,64,65]. Similarly, clinical studies demonstrated patients treated with antipsychotics showed a significant correlation between the genetic variants of H 1 R (rs346074 -rs346070), BMI (body mass index) and obesity [66,67].…”
Section: H 1 R H 3 R and Sga-induced Weight Gainmentioning
confidence: 85%
“…Olanzapine treatment upregulated mRNA expression and protein levels of hypothalamic H 1 R, which was correlated with hyperphagia and weight gain induced by olanzapine [56,64,65]. Similarly, clinical studies demonstrated patients treated with antipsychotics showed a significant correlation between the genetic variants of H 1 R (rs346074 -rs346070), BMI (body mass index) and obesity [66,67].…”
Section: H 1 R H 3 R and Sga-induced Weight Gainmentioning
confidence: 85%
“…[8] Recently, studies in patients treated with antipsychotics showed a significant association of interaction between the genetic variants of H1 receptors (rs346074-rs346070) and BMI and obesity when comparing patients treated with high H1 receptor affinity antipsychotics (olanzapine, clozapine and quetiapine) with those treated with lower H1 receptor affinity antipsychotics (such as aripiprazole). [59] However, earlier studies also reported no relationship between other H1 receptor variants and clozapine-induced weight gain. [60][61] Additionally, in a rat model, both short-(1 week) and long-term (12 weeks) treatment of olanzapine (1.5mg/kg/day, oral), but not haloperidol (0.3mg/kg/day, oral) or aripiprazole (2.25 mg/kg/day, oral), reduced H1 receptor expression in the hypothalamic ARC and VMH, in which the mRNA expression of ARC H1 receptor is significantly correlated with body weight gain and feeding efficiency.…”
Section: The Role Of Histamine and Histamine H1 Receptors In Second-gmentioning
confidence: 94%
“…По актуальным данным, обнаружено, что 20 белковых вариантов CYP3A4, *6, *17, *20 обладают пониженной активностью. Это подтверждается исследованием, в котором добровольцы принимали кветипин, при ýтом носители мутации в промоторном регионе гена CYP3A4*1B (-392 G>A) имели значительно более низкую активность фермента [45].…”
Section: гены кодирующие продукты которые участвуют в фармакокинетиunclassified
“…Немногочисленны и противоречивы исследова-ния полиморфизмов генов гистаминовой систе-мы. Найдена связь ОНП rs346074 и rs346070 гена Н 1 -рецептора H1R с набором веса [85]. В то же время существует ряд работ, опровергающих связь полиморфизмов генов рецепторов гистами-на H1R/H2R/H3R с прибавкой массы тела при приеме нейролептиков [86].…”
Section: гены кодирующие продукты которые участвуют в фармакодинамиunclassified
See 1 more Smart Citation